Prognosis and oncogenomic profiling of patients with tropomyosin receptor kinase fusion cancer in the 100, 000 genomes project. (2022) - Bridgewater, John; Jiao, Xiaolong; Parimi, Mounika; Flach, Clare; Stratford, Jeran; Kamburov, Atanas; Schmitz, Arndt A.; Zong, Jihong; Reeves, John A.; Keating, Karen; Bruno, Amanda; Fellous, Marc; et al.
Highlights: NTRK gene fusions are primary oncogenic drivers in various tumor types. Co-occurrence of NTRK gene fusions with other oncogenic alterations is rare. The presence or absence of an NTRK gene fusion doesn't statistically impact survival. Broad panel genomic testing is recommended to identify patients for targeted therapy. Abstract: Introduction: Neurotrophic tyrosine receptor kinase ( NTRK) gene fusions are oncogenic drivers in various tumor types. Limited data exist on the overall survival (OS) of patients with tumors with NTRK gene fusions and on the co-occurrence of NTRK fusions with other oncogenic drivers. Materials and Methods: This retrospective study included patients enrolled in the Genomics England 100, 000 Genomes Project who had linked clinical data from UK databases. Patients who had undergone tumor whole genome sequencing between March 2016 and July 2019 were included. Patients with and without NTRK fusions were matched. OS was analyzed along with oncogenic alterations in ALK, BRAF, EGFR, ERBB2, KRAS, and ROS1, and tumor mutation burden (TMB) and microsatellite instability (MSI). Results: Of 15, 223 patients analyzed, 38 (0.25%) had NTRK gene fusions in 11 tumor types, the most common were breast cancer, colorectal cancer (CRC), and sarcoma. Median OS was not reached in both the NTRK gene fusion-positive and -negative groups (hazard ratio 1.47, 95% CI 0.39–5.57, P  = 0.572). A KRAS mutation was identified in two (5%) patients with NTRK gene fusions, and both had hepatobiliary cancer. High TMB and MSI were both more common in patients with NTRK gene fusions, due to the CRC subset. While there was a higher risk of death in patients with NTRK gene fusions compared to those without, the difference was not statistically significant. Conclusion: This study supports the hypothesis that NTRK gene fusions are primary oncogenic drivers and the co-occurrence of NTRK gene fusions with other oncogenic alterations is rare.